2018
DOI: 10.12693/aphyspola.133.1129
|View full text |Cite
|
Sign up to set email alerts
|

Application of Intrinsic Quantized Flux of Electrons and Holes in Josephson Junctions

Abstract: The aim of this study is to investigate the influence of spin degrees of freedom on the flux quantization in a 2D Josephson junction. One of the most important properties of the Josephson structures is the total quantum flux which can be related to the phase difference across the junction. For example the sign of the phase difference controls the direction of the Josephson current while the magnitude of the phase difference affect the critical current itself. So far in literature to calculate the total quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…When an electron is placed in an external magnetic field B, during the cyclotron period T c it completes one turn around the cyclotron orbit, but it spins ( s ω ) times about itself ( Figure 1) [13]. We will see that ( s c ω ω  ).…”
Section: Formalismmentioning
confidence: 87%
See 1 more Smart Citation
“…When an electron is placed in an external magnetic field B, during the cyclotron period T c it completes one turn around the cyclotron orbit, but it spins ( s ω ) times about itself ( Figure 1) [13]. We will see that ( s c ω ω  ).…”
Section: Formalismmentioning
confidence: 87%
“…Recently we have calculated the magnetic field inside a free electron due to spinning motion [1] and showed that it is about 8.3 × 10 13 T. This field is about 8.3 × 10 11 times bigger than the highest magnetic field obtained in today's laboratories [2] [3] and 10 3 times bigger than that in neutron stars (magnetars) [4] [5]. In that calculations [1], which are based on the current loop model, the intrinsic magnetic flux associated with its spinning motion of the electron which is calculated either by a semiclassical methode or by a full quantum mechanical solution of Dirac equation [6] [7] [8] gives the same result: ( ) 2 Journal of Modern Physics to that spherical charge distribution.…”
Section: Introductionmentioning
confidence: 99%